Mystery unveiled: Diacanthodes Singer – a lineage within the core polyporoid clade (2020)
ABSTRACT : Diacanthodes (Polyporales, Basidiomycota) is a fungal genus with stipitate basidiomata and a combination of ornamented and dextrinoid basidiospores that is unique among the poroid fungi. Although some hypotheses based on morphological features speculated about the phylogenetic relationships of the taxon, they have never been tested based on molecular data. We performed molecular phylogenetic analyses including specimens of Diacanthodes from the Neotropics and Africa using the internal transcribed spacers (ITS1-5.8S-ITS2 ¼ ITS) and the D1–D2 domains of the 28S gene of the nuclear rDNA regions, as well as the translation elongation factor 1-alpha (TEF-1a) protein-coding gene. Our study revealed Diacanthodes as a member of the ‘core polyporoid’ clade within the Polyporales. Two new species from South America: Diacanthodes cerebriporoides and D. neotropicalis, a new combination D. coffeae from Africa and notes on the other Diacanthodes species are presented. Basidiospore morphology in Diacanthodes and related genera is discussed in the phylogenetic context.